Computer-supported collaborative learning best practices and principles for instructors - Orvis, Kara L.; Lassiter, Andrea L. R.; Gale Group (Hershey, Penn. Information Science Pub., 2007)
Explores techniques that facilitate effective collaborative learning in virtual environments. Provides information on the role of the instructor in computer-supported collaborative learning, real-world perspectives on virtual learning group collaboration, and supporting learning group motivation.
Designing web-based training courses to maximize learning -- Collaborative vs. cooperative learning: the instructor's role in computer supported collaborative learning -- Developing a community of practice in an online research lab -- The case method and collaborative learning -- Preparing online instructors: beyond using the technology -- Collaborative work in online learning environments: critical issues, dynamics, and challenges -- The social psychology of online collaborative learning: the good, the bad, and the awkward -- Collaborative learning among faculty: using course management systems to support faculty development -- Development of online distributed training: practical considerations and lesson learned -- Gender and diversity in collaborative virtual teams -- Student motivation in international collaboration: to participate or not to participate? -- Help me, help you: a triple track approach to maximizing collaborative learning in complex, cross-national virtual teams -- Developing shared mental models in computer-supported collaborative learning -- Practical strategies for assessing the quality of collaborative learner engagement.
Electronic reproduction.
Keywords: Group work in education; Computer-assisted instruction; Web-based instruction; Electronic books